The Times They Are A-Changin’: Heterochrony in Plant Development and Evolution - Buendía-Monreal, Manuel; Gillmor, C. Stewart (Frontiers in Plant Science, 2018)
Alterations in the timing of developmental programs during evolution, that lead to changes in the shape or size of organs, are known as heterochrony. Heterochrony has been widely studied in animals, but has often been neglected in plants. During plant evolution, heterochronic shifts have played a key role in the origin and diversification of leaves, roots, flowers and fruits. Heterochrony that results in a juvenile or simpler outcome is known as paedomorphosis, while an adult or more complex outcome is called peramorphosis. Mechanisms that alter developmental timing at the cellular level affect cell proliferation or differentiation, while those acting at the tissue or organismal level change endogenous ageing pathways, morphogen signaling, and metabolism. We believe that wider consideration of heterochrony in the context of evolution will contribute to a better understanding of plant development.